Digital Information and Navigation Kiosk Application Based on Progressive Web Apps and Leaflet Technology - Adam, Stenly Ibrahim; Lontaan, Rolly Junius; Supit, Vincent Vian; Kolibonso, Shyalenn Cerolin (CogITo Smart Journal, 2024)
Digital information and navigation kiosk applications offer a solution for communities to access updated information and navigate to locations within a specific environment. This app allows users to easily search for and access information about various locations such as lecture halls or faculty residences. The Agile Software Development method was used in the development of the app, facilitating rapid, iterative progress, and quick adjustments based on user feedback. The application provides details regarding various administrative departments and features for searching locations, accessing information, and identifying points of interest. Designed as a Progressive Web App (PWA) and Leaflet Technology, it combines the best features of web and mobile applications, allowing users to access them through a web browser while providing offline capabilities and an app-like user experience. The PWA design ensures that the app is fast, reliable, and can be accessed from any device using a web browser. This enables efficient information dissemination and rapid navigation within the environment.